Kajian Pemenuhan Kebutuhan Air Bersih Melalui Pemanfaatan Air Tanah Individual Pada Rumah-Rumah Kos Di Kawasan Pendidikan Tinggi Tembalang - Clara Aprilia Sinurat; Mardwi Rahdriawan (Jurusan Perencanaan Wilayah dan Kota, 2016)
University region in Tembalang has scale services up to a national scale sothat attract many students from various regions. Thus occurred the temporary migrationprocesses that affecting the development of the activity of living or residing, and the landuse. The increasing number of people/students and the high needs of boarding houseseffect on the improvement of infrastructure needs, especially clean water. Provision ofclean water in settlements around the University region in Tembalang still not fulfilledoptimally. PDAM only able to meet the needs of houses as much as 30% and reach islimited to the downtown area. That makes the boarding houses in the University regionin Tembalang choose to seek clean water through the utilization of ground water. Thepurpose of this study is to investigate the characteristics of the water that produced fromgroundwater utilization individually by the boarding houses in meeting their needs andthe role of stakeholders in response to a such activity. The method used in this research isa combination method/mix method with Sequential Explanatory Design models that usequantitative and qualitative methods which combined sequentially. Most of the boardinghouses that use ground water, water needs can be met in terms of quantity and quality.So it is necessary the action of stakeholders with the goal of supply the clean water andcontrolling the rate of utilization of ground water and increase groundwater infiltrationto stay balanced.